Cryo-EM structural analysis of FADD:Caspase-8 complexes defines the catalytic dimer architecture for co-ordinated control of cell fate - Joanna L. Fox (Nature Portfolio, 2021)
The core FADD:Caspase-8 complex and its regulatory partners, such as the cell death inhibitor c-FLIP, coordinate cell fate. Here authors present the structure of full-length procaspase-8 in a complex with FADD and reveal how recruitment of c-FLIPS into this complex inhibits Caspase-8 activity.